Dipeptidyl-Peptidase IV (DPP IV/CD26)-Activated Prodrugs: A Successful Strategy for Improving Water Solubility and Oral Bioavailability - Velazquez, Sonsoles; de Castro, Sonia; Diez-Torrubia, Alberto; Balzarini, Jan; Camarasa, Maria-Jose (Current Medicinal Chemistry, 2015)
In the search of novel enzyme-based prodrug approaches to improve pharmacological properties of therapeutic drugs such as solubility and bioavailability, dipeptidyl-peptidase IV (DPP IV, also termed as CD26) enzyme activity provides a previously unexplored successful prodrug strategy. This review covers key aspects of the enzyme useful for the design of CD26-directed prodrugs. The proof-of-concept of this prodrug technology is provided for amine-containing agents by directly linking appropriate di- (or oligo)peptide moieties to a free amino group of a non-peptidic drug through an amide bond which is specifically hydrolized by DPP IV/CD26. Special emphasis is also made in discussing the design and synthesis of more elaborated tripartite prodrug systems, for further extension of the strategy to hydroxy-containing drugs. The application of this technology to improve water solubility and oral bioavailability of prominent examples of antiviral nucleosides is highlighted.
Keywords: Amine-containing drugs